1995
DOI: 10.2307/1243234
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Economic Efficiency in Pakistani Agriculture

Abstract: The behavioral and stochastic cost frontier functions are applied to estimate cost inefficiency by farms. The behavioral approach satisfies most of the assumptions of dual cost function and the likelihood ratio test rejects the market efficiency hypothesis implying less than optimum use of manures, labor, and fertilizers. A suboptimal use is explained by holding size, education, credit, and subsistence needs. Small farms seem to be more efficient than large farms in the region. A measure of inefficiency based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 15 publications
10
51
1
2
Order By: Relevance
“…Significantly positive coefficient of farm size indicates that inefficiency increases with the increase in farm size, i.e., large farmers are economically less efficient than small farmers. Parikh et al (1995) found the same result concerning farm size while studying economic efficiency in Pakistan agriculture. They said that small farmers seemed to be more efficient than the large farms in the region.…”
Section: Resultssupporting
confidence: 53%
“…Significantly positive coefficient of farm size indicates that inefficiency increases with the increase in farm size, i.e., large farmers are economically less efficient than small farmers. Parikh et al (1995) found the same result concerning farm size while studying economic efficiency in Pakistan agriculture. They said that small farmers seemed to be more efficient than the large farms in the region.…”
Section: Resultssupporting
confidence: 53%
“…Other food crops grown include maize (mainly grown in the south and central-east regions), cassava, sorghum (in the south), beans, groundnut, sweet potatoes and a wide variety of vegetables. Nonetheless, the risk-coping strategies used by farmers in the country, including the use of cassava as an energy-giving food, are insufficient to make the farmers food secure (Parikh & Shah, 1995;Ramaroson Rakotosamimanana, Arvisenet, & Valentin, 2014), and cassava farmers-similar to other farmers-suffer significant losses due to cyclones.…”
Section: The Study Areamentioning
confidence: 99%
“…Prosedur dua langkah telah digunakan untuk meneliti sumber TE dalam berbagai studi (Hallam dan Machado, 1996;Kalirajan, 1991;Parikh et al, 1995). Battese and Coelli, 1988, Battesse dan Coelli, 1995, serta Coelli et al(1998 mengkritik pendekatan ini dan mengemukakan bahwa variabel sosial ekonomi harus dimasukkan secara langsung dalam model frontier produksi karena variabel ini mungkin memiliki dampak langsung terhadap efisiensi.…”
Section: Model Awal Dariunclassified